2023
DOI: 10.3389/fonc.2023.1137620
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of VATS combined with 3D-CTBA in anatomical basal segmentectomy

Abstract: ObjectiveThis study aimed to summarize the clinical application experience of video-assisted thoracic surgery (VATS) combined with three-dimensional computed tomography-bronchography and angiography (3D-CTBA) in anatomical basal segmentectomy.MethodsClinical data of 42 patients who underwent bilateral lower sub-basal segmentectomy by VATS combined with 3D-CTBA in our hospital from January 2020 to June 2022 were retrospectively analyzed; the patients included 20 males and 22 females, with a median age of 48 (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This strategy is an ideal way to verify the vessels or bronchi that are di cult to identify. [10] The vascular and bronchial branching patterns of RS7 have not been summarized because of its small volume and relative independence from RS9. However, when the bronchial and vascular branches of S7a and S7b straddle the inferior pulmonary vein (IPV), the structure of RS7 will be encountered rst when conducting RS9 segmentectomy through the inferior pulmonary ligament approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy is an ideal way to verify the vessels or bronchi that are di cult to identify. [10] The vascular and bronchial branching patterns of RS7 have not been summarized because of its small volume and relative independence from RS9. However, when the bronchial and vascular branches of S7a and S7b straddle the inferior pulmonary vein (IPV), the structure of RS7 will be encountered rst when conducting RS9 segmentectomy through the inferior pulmonary ligament approach.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative atelectasis occurred in 2 cases (7.4%), pneumonia in 3 cases (11.1%), hemoptysis in 1 case (3.7%), and prolonged air leakage (> 7day) in 1 case (3.7%), all of which were improved after conservative treatment. The median postoperative drainage time was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11) days, and the median length of postoperative hospital stay was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) days. Final pathologies of lesions included minimally invasive adenocarcinoma (MIA) in 21 cases (77.8%) and adenocarcinoma in situ (AIS) in 6 cases (22.2%)(Table 2).…”
Section: Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohtaki et al analyzed a case series of 53 cases of complex segmentectomy compared to 65 cases of simple segmentectomy for the left upper division and reported that complex segmentectomy resulted in less blood loss volume, less major complication, and similar surgical time and duration of postoperative chest drainage and concluded that complex segmentectomy can be performed safely under the guidance of 3D-CT simulation [29]. Zhang et al assessed a case series including 42 cases of VATS anatomical complex segmentectomy for the basal segment and reported that 3D-CT simulation contributed to safe and feasible surgical procedures without conversion to open thoracotomy or lobectomy [30].…”
Section: D-ct Simulation For Clinical Case Seriesmentioning
confidence: 99%